Aeromonas sobria peritonitis in a peritoneal dialysis (PD) patient: a case report and review of the literature - Panai Song; Jun Deng; Tao Hou; Xiao Fu; Lei Zhang; Lin Sun; Yinghong Liu (BMC Nephrology, 2019)
Abstract Background Peritonitis is a common cause of catheter removal and mortality in the patient undergoing peritoneal dialysis (PD). Various pathogenic organisms have been identified as the etiology of PD-related peritonitis, among which Aeromonas sobria is a rare one. Several studies have indicated that Aeromonas sobria might be of particular clinical significance because of its enterotoxin production. We here present a case of peritonitis due to Aeromonas sobria in a PD patient and review of the related literature. Case presentation A 37-year-old man with chronic renal failure who was secondary to chronic glomerulonephritis had been on PD for approximately 6 months without any episode of peritonitis. In July 2015, he was admitted to the hospital for fever, vomiting, abdominal pain, diarrhea and cloudy dialysate several hours after eating stinky tofu. The peritoneal effluent culture yielded Aeromonas sobria. The patient was given intraperitoneal amikacin and intravenous levofloxacin for 10 days. And the patient’s symptoms such as diarrhea, abdominal pain were relieved and the cloudy effluent turned to be clear. Unfortunately, peritoneal dialysis catheter was blocked because of fibrin clot formation in the setting of inflammation, and finally it was removed. Conclusions Aeromonas species are rare causes of PD-related peritonitis, however they should not be ignored. Clinicians should be aware of monitoring the hygiene protocol and retraining patients at regular intervals, especially for such rare cases.